Tax Compliance Models: From Economic to Behavioral Approaches - Larissa Margareta BĂTRÂNCEA; Ramona Anca NICHITA; Ioan BĂTRÂNCEA; Bogdan Andrei MOLDOVAN (Transylvanian Review of Administrative Sciences, 2012)
The paper reviews the models of tax compliance with an emphasis on economic and behavioral perspectives. Although the standard tax evasion model of Allingham and Sandmo and other similar economic models capture some important aspects of tax compliance (i.e., taxpayers’ response to increases in tax rate, audit probability, penalty rate) they do not suffice the need for an accurate prediction of taxpayers’ behavior. The reason is that they do not offer a comprehensive perspective on the sociological and psychological factors which shape compliance (i.e., attitudes, beliefs, norms, perceptions, motivations). Therefore, the researchers have considered examining taxpayers’ inner motivations, beliefs, perceptions, attitudes in order to accurately predict taxpayers’ behavior. As a response to their quest, behavioral models of tax compliance have emerged. Among the sociological and psychological factors which shape tax compliance, the ‘slippery slope’ framework singles out trust in authorities and the perception of the power of authorities. The aim of the paper is to contribute to the understanding of the reasons for which there is a need for a tax compliance model which incorporates both economic and behavioral features and why governments and tax authorities should consider these models when designing fiscal policies.